Capitalism, Socialism and Serfdom - Domar, D.Evsey (Newyork Cambridge University Press, 1989)
The collection consists of four parts: Part I presents three non-technical essays on economic development and economic systems. Four out of five essays in Part II deal with the theory and measurement of the so-called Index of Total Factor Productivity for several countries. The fifth essay is on the theory of index numbers. The first essay of Part III compares the American and Soviet patterns of economic development and finds that the path followed by each country might have been optimal for it at the time. The second essay develops a general theory of a producer cooperative. The third essay discusses a method for avoiding monopolistic exploitation, under either system, without price control. Part IV presents three applications of economic theory to historical problems - in particular, to serfdom and slavery. The first, on 'The Causes of Slavery or Serfdom', has become a classic. The second challenges the widely accepted view that Russian serfdom had become unprofitable for the serf-owners before the Emancipation of 1861. The last shows that the oft-repeated estimate of the overcharge for land allotted to the former serfs by the Emancipation has little basis in fact.